Modeling the Dimensions of Globalization, Economic Growth, Inequality, and Poverty in Indonesia Using VAR/VECM Method - Nindien, Qurrota Ayu; Ikhsana, Nadya Ramadhani; Armunanto, Yohanes Novi (Integra: Journal of Integrated Mathematics and Computer Science, 2025)
This study analyzes the relationship between various dimensions of globalization, economic growth indicators, inequality, and poverty in Indonesia using a VECM framework. All variables are stationary at the first difference, and the Johansen cointegration test identifies four cointegrating vectors, indicating a long-run equilibrium among poverty (POV), FDI, inequality (GR), unemployment (UE), economic openness (IEG), economic cooperation (IEC), and social openness (ISG). Based on the Akaike Information Criterion (AIC), a lag order of two is selected, and the VAR stability test confirms that the model is valid. In the long run, FDI, GR, UE, IEG, and ISG significantly influence poverty, whereas IEC shows no significant effect. FDI, IEG, GR, and ISG contribute to poverty reduction, while UE increases poverty. No variable exhibits short-run significance, but the significant error correction term (ECT) reflects a gradual adjustment toward long-term equilibrium. The FEVD results show that up to the tenth period, the variance in POV is primarily explained by POV itself (63.97%), followed by ISG (15.77%), GR (12.76%), and UE (5.49%), whereas FDI, IEG, and IEC contribute less than 1%. Overall, poverty dynamics in Indonesia are largely driven by their own persistence, with additional contributions from social openness and inequality.